(3OjhGf CHj aQGS GdMeOGfis - (3CHh aQGS , GdMGQK Hf SYjO Hf MeOGf GdJZdHj GdQHYj, CHhaQGS GdMeOGfj,J (B357 (3g` s
(3ChdgG (B:s
(3bO cGf HOQ GdJeGe MSfG hGdfGS ai MHg ShGO s
(3BNQgG (B:s
(3CQLhRI ai GdWQO hde JRd SHY djGd YOOG CSYO ef QGL hCMXi ef ZOG s
(3HChdgG JMHjS dCMeO GdefUhQ Ydi NRGfI GdbQhjjf SfI (B1011s
(3HQSe NRGfI CMeO GdefUhQ HNW Ydi Hf efUhQ GdTjXeis
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B156s
Keywords: (3GdCOHs